The impacts of performance related pay (PRP) towards the performance of SMEs workers in Alor Setar, Kedah - Siti Nurhafizah, Shaharuddin (2015)
The aim of this research is to study the impacts of performance related pay (PRP) towards the performance of SMEs workers in Alor Setar, Kedah. The objective of this research is to identify the types of performance related pay used in SME industry and to study the relationship between performance related pay and the performance of SMEs workers. The performance related pay (PRP) will set as the independent variable. Then, the performance of SMEs workers is the dependent variable. 140 respondents from the small and medium enterprise (SMEs) industry in Alor Setar, Kedah were surveyed by questionnaire. The collected data were analyzed by using Cronbach‟s Alpha (reliability analysis), descriptive statistics and by using a computer program called Statistical Package for Social Sciences (SPSS). The significant of this study is to show the impacts of performance related pay (PRP) towards the performance of SMEs workers that has been proven to be helpful in improving the overall performance of workers and the results show that there is a significant positive relationship between the performance related pay (PRP) and the performance of SMEs workers and the finding are in accordance with previous researches.